SWOT Analysis of Augmented Reality Implementation as an Educational Medium for Local Cultural Artifact Preservation Among the Younger Generation - Siska Aprelyani (Greenation Education and Culture Review, 2026)
The preservation of local cultural artifacts faces increasing challenges due to rapid technological advancement and the declining interest of younger generations in cultural heritage. This study aims to analyze the implementation of Augmented Reality (AR) as an educational medium for preserving local cultural artifacts using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) framework. A qualitative descriptive approach was employed by collecting data through literature review, observation, and SWOT analysis to identify internal and external factors affecting AR implementation. The findings indicate that AR offers significant strengths, including interactive visualization, immersive learning experiences, and increased engagement among young users. However, its implementation is constrained by high development costs, device compatibility issues, and limited digital literacy in certain communities. Opportunities arise from the widespread adoption of smartphones, digital transformation initiatives, and government support for cultural preservation. Meanwhile, threats include rapid technological changes, sustainability challenges, and competition from other digital entertainment platforms. The study concludes that AR has strong potential to become an effective educational tool for promoting awareness and appreciation of local cultural heritage among younger generations. Strategic collaboration among educational institutions, cultural organizations, government agencies, and technology developers is essential to ensure the sustainable implementation and continuous development of AR-based cultural education.